2008
DOI: 10.1177/2156759x0801100301
|View full text |Cite
|
Sign up to set email alerts
|

Precursors to the Gender Gap in College Enrollment: Children's Aspirations and Expectations for Their Futures

Abstract: In light of the increasing gender gap in college enrollment, data from two waves of interviews with 115 elementary and middle school children were examined for developmental and gender differences in participants’ aspirations and expectations for their futures. While there were no gender differences in children's educational aspirations or expectations, girls were more likely than boys to aspire to careers that require a college education, more likely to emphasize career advancement in their rationale for atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Age was examined in this study because Kortering, Braziel, and McClannon (2010) found grade level (which is often closely associated with age) to be predictive of post-school employment plans for students with learning disabilities. Gender was incorporated into the study based upon the work of Blackhurst and Auger (2008), who found that females expressed preferences for occupations requiring a college education at rates higher than males. The inclusion of disability was supported by the work of Grigal and Neubert (2004), who discovered significant interactions between type of student disability and parent work and postsecondary expectations for the student.…”
Section: Overview Of Capromisementioning
confidence: 99%
“…Age was examined in this study because Kortering, Braziel, and McClannon (2010) found grade level (which is often closely associated with age) to be predictive of post-school employment plans for students with learning disabilities. Gender was incorporated into the study based upon the work of Blackhurst and Auger (2008), who found that females expressed preferences for occupations requiring a college education at rates higher than males. The inclusion of disability was supported by the work of Grigal and Neubert (2004), who discovered significant interactions between type of student disability and parent work and postsecondary expectations for the student.…”
Section: Overview Of Capromisementioning
confidence: 99%
“…There is clearly a need for future research in this area, however, current CTE policy presumes that students will begin a certain career path early in high school and persist in that field throughout adult life as well. Especially in terms of nontraditional participation, the theory is that if more students are recruited to nontraditional programs, then subsequently, more students will finish nontraditional programs, seek out jobs in nontraditional fields, thus bringing about increased gender balance within the workforce (Blackhurst & Auger, 2008;Teig & Susskind, 2008;Wilbourn & Kee, 2010). However, based upon what is known about student transitions, this calls into question the practicality of such policy expectations.…”
Section: Future Researchmentioning
confidence: 87%
“…School counseling can be especially helpful for young people in terms of increasing their awareness of career options and understanding how their interests and abilities relate to various occupational requirements (Blackhurst & Auger, 2008). However, Gottfredson & Lapan (1997) pointed out that despite the fact that people to form a gender-self concept that will eventually influence their vocational aspirations as young as age six, students do not typically start to receive career counseling until their teen years.…”
Section: Increasing Nontraditional Employmentmentioning
confidence: 99%
See 2 more Smart Citations